Juan Ossio, Ethnography of the Andean culture. Lima: Fondo Editorial del Congreso del Perú. 2018. 514 p. - Huerta-Mercado, Alexander (2018)
The book brings together the works carried out by Juan Ossio over fifty years; developed from his field research, analysis of historical documents and personal testimonies. The author uses the ethnographic and historical method to identify and analyze the common characteristics that articulate different aspects of economic, political, traditional, ritual and kinship organization in the communities of the Andean territory under cultural characteristics that approach a matrix.